The concept of system of an improving (functional) food in fitness. - Tsyganenko O.I (Kharkov National Pedagogical University, 2011)
The literature analysis on the organization of an improving food in fitness is carried out. The concept of system of an improving (functional) food in fitness is developed. The concept includes the purpose and problems of system of an improving food in fitness, principles of its organization, conceptual approaches to the organization of an improving food in fitness. For information support of work of system it is recommended to use the computer program "Olympus".